Anthropology and architecture: union for the future (Research, Society and Development, 2021)
This article shows from research based on studies and analysis of various articles and urban spaces in order to understand how anthropology studies the human being in different areas while architecture also analyzes it and uses anthropological studies to design urban space and the home of each citizen, together with several analyzes of shape and colors capable of stimulating the needs and actions of the users. Thus, the work aims to clarify the need for anthropological studies in urban and housing projects. Concluding, then, that with a deeper investigation of the two disciplines, the importance of one to the other becomes noticeable and how a discipline could be created in which the debate of both unites so that the urban space becomes increasingly welcoming and useful, decreasing social problems, in addition to being more comfortable and sustainable for individuals and the environment.